Pertanggungjawaban Pidana Bagi Pelaku Tindak Pidana Pencurian Data Nasabah Perbankan dengan Mode Skimming Ditinjau dari Undang-Undang Nomor 1 Tahun 2024 Tentang Informasi dan Transaksi Elektronik - Ludgardis Goo Nembo; Bhisa Vitus Wilhelmus; Debi F.Ng. Fallo (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Banking is one of the financial services companies that has provided services to the community and businesses, Behind this development there are various legal problems related to information crime and electronic transactions in the banking sector, Skimming is the act of stealing debit or credit card information by accessing an independent cash machine and copying the information contained on the magnetic stripe of the debit card or credit belonging to the customer (victim) illegally to have control over the customer's (victim) account. The application of the law to the crime of ATM skimming is regulated in Article 362 of the Criminal Code (KUHP) regarding the crime of theft. This research is a type of normative judicial research supported by a normative approach by using primary legal materials, secondary legal materials and tertiary legal materials as data sources. This study uses a prescriptive method, which is an analysis method that provides an assessment (justification) about the object being researched whether it is true or false, or what should be according to the law. The results of the study show that (1) Skimming is a magnetic stripe crime that exists on ATM cards illegally to have control over the card or the account by duplicating the ATM card or by installing a hidden camera to find out the ATM PIN of the customer or victim. (2) Strategies to prevent unauthorized access and early detection of suspicious activities can be applied to reduce the incidence of criminal acts and effective cyber security is to strengthen the network and security system. This can include investing in cutting-edge security technologies, such as robust firewalls, active network monitoring, and security programs that can detect suspicious attacks. In addition, organizations also need to involve their employees in cybersecurity efforts.